2017
DOI: 10.1093/europace/eux205
|View full text |Cite|
|
Sign up to set email alerts
|

Symptomatic atrial fibrillation and risk of cardiovascular events: data from the Euro Heart Survey

Abstract: Persistence or development of symptoms after medical treatment are associated with an increased risk of CV events during a 1-year follow-up. Type of AF, along with hypothyroidism, COPD and chronic heart failure are significantly associated with symptoms persistence despite medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 20 publications
1
22
0
3
Order By: Relevance
“…The recommended AF rhythm control in the current guidelines is intended for patients with symptomatic AF rather than ECG‐based AF 30,31 . However, AF progression to PeAF or permanent AF is accompanied by high cardiovascular risk and long‐term mortality 32,33 . In addition, metabolic syndrome, which is associated with AF progression, increases the nonthromboembolic adverse cardiac outcomes in patients with AF 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The recommended AF rhythm control in the current guidelines is intended for patients with symptomatic AF rather than ECG‐based AF 30,31 . However, AF progression to PeAF or permanent AF is accompanied by high cardiovascular risk and long‐term mortality 32,33 . In addition, metabolic syndrome, which is associated with AF progression, increases the nonthromboembolic adverse cardiac outcomes in patients with AF 34 .…”
Section: Discussionmentioning
confidence: 99%
“…3,5% всего населения. Социальное значение данной патологии во многом определяется серьезными ее осложнениями, включающими инсульт, системные тромбоэмболии, когнитивные нарушения, которые повышают смертность, снижают качество жизни пациентов и приводят к повышению затрат на лечение [2][3][4][5]. Одним из основных направлений терапии при ведении пациентов с ФП является контроль частоты желудочковых сокращений (ЧЖС).…”
Section: Discussionunclassified
“…However, the authors observed a comparable distribution of digoxin use between patients in EHRA class 1 and those in EHRA class >1. In contrast, a greater supply with digitalis was observed in symptomatic patients than in asymptomatic patients among 2,452 originally symptomatic AF patients at after 1 year of follow-up [34]. The authors of that study found increased risks of cardiac rehospitalization, stroke, and HF, worsening among patients with symptomatic AF.…”
Section: Discussionmentioning
confidence: 99%